Monkeypox: generalities, transmission method and therapeutic approaches (Research, Society and Development, 2022)
Clinical and epidemiological studies suggest that human-to-human transmission of monkeypox may occur through direct or indirect contact, through secretions through the respiratory tract or through skin lesions, and through contaminated objects. Therefore, this literature review exposes generalities, forms of transmission and therapeutic approaches related to Monkeypox. A survey was carried out on government websites, scientific articles and journalistic websites about ways of prevention and vaccines against the monkeypox virus. It is known that this zoonosis belongs to the Poxviridae family and spreads with greater intensity in underdeveloped countries, due to the unsanitary conditions of these places. Studies indicate that vaccines produced for smallpox are efficient against Monkeypox virus, especially the third generation ones. The vaccine that obtained a better result in the research was the MVA-BN, since it does not leave lesions in the place where it was applied and does not present a threat to a possible transmission, it was also developed for immunosuppressed individuals, facilitating the mass vaccination of the vaccine. population. Some drugs have also been shown to be effective against Monkeypox, namely: Brincidofovir, Cidofovir and Tecovirimat, with Tecovirimat in evidence for its efficiency and moderate side effects.